HYDROCELE OF THE CANAL OF NUCK: A RARE DEVELOPMENTAL ANOMALY - Mathangasinghe, Yasith; Kalubowila, J.N. (Sri Lanka college of Radiologist, 2018)
Introduction Hydrocele of the Canal of Nuck is a developmental abnormality in females characterized by accumulation of fluid in a patent peritoneal extension along the round ligament of the uterus. Approximately 400 cases of this entity have been reported worldwide1 . This has no been reported previously in Sri Lanka.
Keywords: Canal of Nuck, Hydrocele